INTERAKSI SIMBOLIK KOMUNITAS TARING BABI DENGAN MASYARAKAT SEKITAR - Dipa, Satria Wijaya (Jurnal Insani, 2018)
This research is motivated by the interest of researchers in the symbolic interaction of theTaring Babi Community who look eccentric with the surrounding community. The purpose of this study was to find out the intercultural communication that was built by the Taring Babi Community with the society. The research method used is a qualitative method with descriptive analysis. Therefore, to fulfill the available data, the researcher selected three informants in this study were taring babi, formal figures and informal figures. Selection of informants using purposive sample technique, while data collection techniques through interviews, observation and documentation. Examination of data validity is done using source triangulation and technical triangulation. The result of this study indicate that intercultural communication made the Taring Babi Community can be accepted by surrounding community.